MODEL UNTUK UJI KUALITAS SISTEM INFORMASI UJIAN NASIONAL BERBASIS KOMPUTER TINGKAT SMA & MA - Sobari, Irwan Agus; Akbar, Fajar; Zuama, Robi Aziz; Rais, Amin Nur (Jurnal Pilar Nusa Mandiri, 2018)
UNBK (Ujian Nasional Berbasis Komputer) is a developing national examination application that has claimed the attention and interest of researchers in the development of computer science in the world of education. One of the most recent developments received at UNBK is its usefulness. We propose a successful model model for DeLone & McLean IS to analyze the quality of UNBK at the usefulness of its users. The empirical approach is based on an online survey questionnaire for high school & MA students, the results of feedback received as many as 74 individuals. The results reveal that Information Quality, System Quality and Service Quality are important precedents of user satisfaction, and the importance of user satisfaction will produce significant net benefits. Understanding the importance of the context of UNBK on Net Benefit for users is useful to provide new insights to relevant agencies to implement strategies to retain users or even attract potential adopters. this study provides theoretical and practical implications from the research findings.